More than meets the eye? Factors that affect target selection by plant miRNAs and heterochromatic siRNAs. (October 2015) - Wang, Feng; Polydore, Seth; Axtell, Michael J
Highlights: Several exceptions to the canonical plant miRNA-target base pairing rules have been described. Factors besides complementarity are likely to influence miRNA targeting in plants. Pol V is required for heterochromatic siRNA targeting, but its RNAs are elusive. Pre-existing DNA methylation is required for Pol V genomic occupancy. Abstract : MicroRNAs, which target mRNAs for post-transcriptional regulation, and heterochromatic siRNAs, which target chromatin causing DNA methylation, make up the majority of the endogenous regulatory small RNA pool in most plant specimens. They both function to guide Argonaute proteins to targeted nucleic acids on the basis of complementarity. Recent work on plant miRNA-target interactions has clarified the general ''rules' of complementarity, while also providing several intriguing exceptions to these rules. In addition, emerging evidence suggests that several factors besides miRNA-target complementarity affect plant miRNA function. For heterochromatic siRNAs, recent work has made progress towards comprehensively identifying potential target regions, but numerous fundamental questions remain to be answered.